OPPORTUNITY COST ARE A KEY TO CASH PUZZLE OF THE COMPANY - S. I. Lutsenko (Real Economics Publishing House, 2015)
Features of influence of opportunity cost on the cash policy of the Russian companies are considered. The author analyzes relationship of cause and effect of escalating of cash. The author researched features of a choice the Russian companies of sources of financing. The author shows that availability of opportunity costs forces the companies to be reoriented on internal sources of financing. Opportunity costs are the indicator for a choice of optimum financing. The model (specification) presented in work is tested for determination of its adequacy, from the point of view of quality of forecasting. It is estimated three kinds of specifications: pooled regression, regression with a random effect and regression with the fixed effect. The purpose of work attempt to open cash puzzle of company disclosing of a puzzle. That is, to reduce opportunity costs for preserving of cash as the preventive motive, allowing to struggle with financial restrictions. Novelty of the presented work consists that the companies can rationally manage cash holdings, using negative shocks (signals) in the capital market, to expect them and without supposing the situations connected with financial restrictions.